GE_GERICHTE P/24493/2020 vom 10. Dezember 2021 - GE Cour de justice (2021)
VOL(DROIT PÉNAL);ENTRÉE ILLÉGALE;SÉJOUR ILLÉGAL;DOCUMENT DE VOYAGE;EXPULSION(DROIT PÉNAL) | CP.139.ch1; CP.139.ch1; CP.22.al1cum; LEI.115.al1.leta et b; OEV.8; OAJA.9.al2; CP.66.alabis